Expanding the Game Design Space - Teaching Computer Game Design in Higher Education - Lasse Juel Larsen; Gunver Majgaard (Stockholm University Press, 2016)
This article considers game design research in educational settings. Its focus is on how undergraduate students - particularly engineering students - learn computer game design. From observations conducted during our game design courses we have developed a model of expanded game design space. It encapsulates the entire development process from the first ideas to the final game with emphasis on game design thinking. Our model of expanded game design space consists of four separate - yet interconnected - layers in the process of game development. The first layer addresses the importance of framing, providing a clear game design assignment that involves the formulation of intended player experience and a description of game mechanics. The second layer focuses on game design thinking from six different aspects of game design chosen in relation to the framing of the game design assignment. The third layer establishes correspondence between formal elements of computer games and the structure of problem-based creativity. It addresses how game design challenges should be formulated and how creative solutions can be measured. The fourth and final layer demonstrates how clear framing can act as a guideline for evaluating game design thinking and for measuring solutions made in the development process. To strengthen our model of expanded design space, we will present examples from our game design courses.